Analisis Pemikiran Al-Ghazali pada Konteks Komunikasi dalam Dakwah: Studi Pustaka - putri, rifania rifania (Komunika: Journal of Communication Science and Islamic Dakwah, 2025)
Doing da’wah amar ma’ruf nahi mungkar is a noble thing. Therefore, this da’wah is meaningful in the sight of Allah. In addition, da’wah is also the subject of religion, so it is important to do it. Da’wah amar ma’ruf nahi munkar must be done with full readiness. And in the process, the method used must be really structured, because the purpose of this da’wah is to prevent disobedience and evil, eradicate crime, and invite others to return to the way of Allah. The problem studied in this study focuses on the communication pattern of Imam Al-Ghazali’s da’wah which is based on three legal sources, namely the Qur’an, Hadith, and Atsar. The goal is to analyze in depth how the stages that can be used in da’wah amar ma’ruf nahi munkar. This research is a qualitative methodological research using library research and observation. The results of the qualitative research show that the communication pattern of Imam Al-Ghazali’s da’wah is explained in the discussion of the ihtisab method. Ihtisab is a method of proselytizing amar ma’ruf nahi munkar in which there are ten themes of stages, namely ta’arruf, ta’rif, prohibition, rebuke, preventing by hand, tahdid & takhwif, preventing with limbs or objects, war. The ten themes must be carried out in a coherent manner so that the results are maximized and do not cause chaos afterward. In writing, the researcher realizes that there are still shortcomings in the solution. Therefore, this research is expected to be a basic reference for a deterrent to evil and can be continuously updated by further researchers. This is so that Imam Al-Ghazali’s method of da’wah is not forgotten even though it is consumed by the times. And with the renewal, Imam Al-Ghazali’s da’wah method can still be used even though the times have changed.